Evaluating the impact of the travel ban within mainland China on the epidemic of the COVID-19. (June 2021) - Xue, Ling; Jing, Shuanglin; Sun, Wei; Liu, Maoxing; Peng, Zhihang; Zhu, Huaiping
Highlights: We developed a mobility network model for spatial epidemics. The second outbreak occurred approximately on March 1, 2020. By March 15, 2020, the cumulative cases increased by 70.6% without a travel ban. The increase of cumulative cases is mainly caused by intra-province travel. The strict travel ban successfully prevented a severe secondary wave in China. Abstract: Objectives: The ongoing COVID-19 pandemic expanded its geographic distribution through the movement of humans and caused subsequent local outbreaks. Hence, it is essential to investigate how human mobility and travel ban affect the transmission and spatial spread while minimizing the impact on social activities and national economics. Methods: We developed a mobility network model for spatial epidemics, explicitly taking into account time-varying inter-province and inner-province population flows, spatial heterogeneity in terms of disease transmission, as well as the impact of media reports. The model is applied to study the epidemic of the dynamic network of 30 provinces of mainland China. The model was calibrated using the publicly available incidence and movement data. Results: We estimated that the second outbreak occurred approximately on February 24, 2020, and the cumulative number of cases as of March 15, 2020, increased by 290.1% (95% CI: (255.3%, 324.9%)) without a travel ban in mainland China (excluding Hubei and Tibet). We found that intra-province travel contributes more to the increase of cumulative number of cases than inter-province travel. Conclusion: Our quantitative and qualitative research results suggest that the strict travel ban has successfully prevented a severe secondary outbreak in mainland China, which provides solutions for many countries and regions experiencing secondary outbreaks of COVID-19.